Yoghurt : science and technology - Tamime, A. Y. (CRC Press ; Woodhead Pub., 1999)
The new edition includes a discussion of 'bio-yoghurts' with their important implication for manufacturing practice. Contents include: Background to manufacturing practice; Processing plant and equipment; Cleaning and hygiene; Traditional and new developments in yoghurt production; Microbiology of yoghurt and 'bio' started cultures; Biochemistry of fermentation; Preservation and production of starter cultures; Nutrition; Quality control and HACCP.
Keywords: Yogurt.; elektronické knihy; electronic books